Self Determination and Engagement of Social Studies Students in the Selected Private Schools - Ranoco, Joann E. (International Journal on Integrated Education, 2025)
This study explores the relationship between student engagement and self-determination in Social Studies classes among senior high school students in selected private schools in Cabuyao, Laguna. Grounded in the Engagement Theory and Self-Determination Theory, the research examines how aspects of engagement—relating, creating, and donating—and components of self-determination—autonomy, competence, and relatedness—interact to shape students' academic experiences. Employing a quantitative correlational research design, the study collected data from 50 randomly selected students through validated survey questionnaires. The results indicated that students demonstrated very high levels of both engagement and self-determination. Furthermore, a significant positive correlation was found between these two constructs. These findings suggest that enhancing student engagement and supporting self-determined learning can positively influence motivation, participation, and academic performance. In response to the results, an action plan was developed to guide educators in designing more interactive and student-centered Social Studies learning environments. The study adds to the existing body of literature on student motivation and proposes practical strategies for integrating student voice and real-world relevance into classroom instruction to promote deeper academic involvement and civic consciousness.